Strategic Management in Increasing Educational Participation for 12-year Compulsory Education - Dadan F Ramdhan; Isop Syafe’i (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2019)
In Indonesia, education has many problems to take into consideration. One of them is that SMP (Sekolah Menengah Pertama/Junior high school) graduates could not continue to SMA (Sekolah Menengah Atas/Senior high school) level. This research was aimed at investigating accurate data and information regarding strategic management administered by education and culture office of Sukabumi city in improving educational participation. This research applies strategic management model proposed by Hunger-Wheelen. This study was qualitative using case study. Data were collected using interview, documentation, and observation. The Education and Culture Office of Sukabumi City had no specific vision and mission for the implementation of 12-year secondary education. The strategies included providing financial support in many programs like kartu pintar, Direct Help Card, and scholarships for poor families. The implementations were based on programs, budgets and procedures. In general, the implementation had been successful but it has two programs which had not succeeded namely retrieval program and program to support student who were prone to drop out. Strategy evaluation was done according to the system, types, and the management.